SOLID INFECTIOUS WASTE MANAGEMENT PRACTICES IN A GOVERNMENT HOSPITAL IN CENTRAL KALIMANTAN, INDONESIA - Cindy Dwi Septiana Simangunsong; Bambang Yulianto; Ferry Hermawan (RADJA PUBLIKA, 2025)
Solid infectious waste management is a crucial aspect of environmental and public health in healthcare facilities. This study aimed to analyze the solid infectious waste management practices at a public hospital in Central Kalimantan based on the Regulation of the Minister of Environment and Forestry (PermenLHK No. P.56/MenLHK-Setjen/2015). This study used a qualitative descriptive approach, including observations, interviews, and document review. Results indicated compliance in segregation, separation, and treatment, while temporary storage was non-compliant, as waste was placed directly in the incinerator area instead of the designated Hazardous Waste Temporary Storage (TPS Limbah B3) which potentially poses environmental risks. Waste generation increased annually, averaging 0.4–0.8 kg/bed/day. It is recommended that the hospital optimize temporary storage, enhance staff capacity through training, and conduct regular waste monitoring to ensure effective and sustainable treatment planning.